The Computer Numerical Control System Design for the Saddle Surface of the Flange Connection Processing Plant - Qian, Ruiwei; Feng, Yan; Ren, Yongfeng; Yang, Dongfang (Journal of physics. Conference series, 2021)
It is required to construct huge hydrocracking units in order to boost the revenue from refined goods. The barrel welding receiver skirt has a saddle-shaped surface in the reactor processing of the barrel welding receiver skirt, and the processing process is getting increasingly complex. In order to enhance the welding quality of the skirt to the actual form of the receiver as the size and wall thickness of the receiver grow, it is important to develop the CNC system for welding the skirt to the actual shape of receiver. It talked about the manufacturing plan, the hardware circuit, and the software flowchart, to name a few subjects. Finally, the C programming language and the assembles programming language are utilized to implement the manufacturing flowchart in uVision3. Protues8 is responsible for the implementation of the hardware circuit. It is demonstrated by the simulation results that the proposed design plan for the CNC system is technically possible.